Control a pneumatic sequence using waterfall method in the LabVIEW plataform - Simões, José (2016)
The project chosen for this paper was one that the student had to construct a program using the LabVIEW platform in which it would control electro pneumatic systems using the waterfall method. As a result a program was created in LabVIEW that would do just that with various other functionalities like an interactive GUI (guided user interface) which is easy to follow and use along with microcontroller communication and programming capabilities. This added functionality allows the user to export the pneumatic code to a microcontroller like the NI USB 6009 (used in this project) and test or execute the code using pneumatic cylinders and end position sensors.